2007
DOI: 10.1177/000312240707200505
|View full text |Cite
|
Sign up to set email alerts
|

The Implications of Racial Misclassification by Observers

Abstract: M ost research on "race" measures race using a respondent's self-identification. As researchers, we commonly use this measure as a proxy for many things, including an individual's racial identity and how an individual is perceived by others. But this entails a fundamentally flawed assumption: that individuals' self-identification consistently matches how others perceive them. In reality, our perceptions of others are unquestionably biased by our own characteristics (Harris 2002;Hill 2002). Moreover, given the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
191
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 149 publications
(198 citation statements)
references
References 34 publications
6
191
0
1
Order By: Relevance
“…Consistent with previous reports of racial misclassification prevalence, 12 such a discord was relatively common among Nanic groups were primarily driven by groups in which the racial/ethnic incongruence was more common.…”
Section: Perceived Discrimination In Health Care -Stepanikova and Oatessupporting
confidence: 90%
See 1 more Smart Citation
“…Consistent with previous reports of racial misclassification prevalence, 12 such a discord was relatively common among Nanic groups were primarily driven by groups in which the racial/ethnic incongruence was more common.…”
Section: Perceived Discrimination In Health Care -Stepanikova and Oatessupporting
confidence: 90%
“…In one study, more than a third of self-identified Native Americans were classified by interviewers as another racial group, and the discrepancy was linked to negative mental health outcomes. 12 In another study, the discord between self-identified and interviewer-attributed race was associated with poorer health, especially among those who self-identified as White but reported that others perceived them as non-White. 13 Among self-identified Hispanics, socially assigned Whites had better health compared with socially assigned Hispanics; among self-identified Native Americans, socially assigned Whites had better health compared with socially assigned Native Americans; and among multi-…”
Section: Introductionmentioning
confidence: 96%
“…Apart from socioeconomic characteristics, a link between inconsistent categorization and health has also been discovered: Campbell and Troyer (2007) show evidence that self-classified American Indians experience high rates of psychological distress when classified as a member of another category by the observer. Finally, Stepanikova (2010) finds that being classified as a lower-status racial group by others is associated with negative physical and mental outcomes.…”
Section: Racial Inconsistenciesmentioning
confidence: 99%
“…R ECENTLY, a growing number of studies has been concerned with racial fluidity, providing evidence that individual race is changeable, contextual, and multidimensional (Telles and Lim 1998;Harris and Sim 2002;Hitlin, Brown, and Elder 2006;Ladányi and Szelényi 2006;Campbell and Troyer 2007;Saperstein and Penner 2012). Focusing on multidimensionality, observed race (one's race as classified by others) and its differences from racial self-classification have received significant attention (see Roth 2016).…”
mentioning
confidence: 99%
See 1 more Smart Citation